2012
DOI: 10.1159/000339611
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mixed Adenoneuroendocrine Carcinoma with a Trilineage Cell Differentiation: Case Report and Review of the Literature

Abstract: Most gastric neuroendocrine tumours are well differentiated and considered as neuroendocrine neoplasms, whilst poorly differentiated lesions are considered as neuroendocrine carcinomas and account for only 6–16% of gastric neuroendocrine tumours. Gastric mixed adenoneuroendocrine carcinomas are rare malignancies usually composed of a neuroendocrine carcinoma and an adenocarcinoma with a variable grade of differentiation. Here, we report an unusual and rare gastric mixed adenoneuroendocrine carcinoma with a tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…In cases with distant metastases, a combination of cisplatin and etoposide had been recommended. Pericleous et al [ 15 ] reported a case of gastric MANEC with trilineage cell differentiation treated palliatively with long-acting somatostatin analogues. However, the optimal treatment policy is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with distant metastases, a combination of cisplatin and etoposide had been recommended. Pericleous et al [ 15 ] reported a case of gastric MANEC with trilineage cell differentiation treated palliatively with long-acting somatostatin analogues. However, the optimal treatment policy is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the clinical characteristics of gMANEC largely depend on the proportion of neuroendocrine carcinoma components [36,37]. Fernandes et al believe that the prognosis of gMANEC might be related to whether certain tumor components are more invasive [38]. Furthermore, previous studies have con rmed that sarcopenia is associated with the long-term prognosis of gastric adenocarcinoma patients [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…gMANEC is de ned as a malignant tumor with morphological components of glandular epithelial cells and neuroendocrine cells, both of which account for at least more than 30% of the total cells [4]. The clinical characteristics of gMANEC generally depend on the proportion of neuroendocrine carcinoma components [38,39]. Fernandes et al postulated that the prognosis of patients with gMANEC might be related to whether certain tumor components are more invasive [40].…”
Section: Discussionmentioning
confidence: 99%